Develop Creative Brick Kiln Cultural Products by Powder Metallurgy Process Technique. Issue 1 (September 2020) - Lee, Yann-Long; Hung, Yu-Ching; Chou, Wen-Chih; Wang, Chuan-Po; Peng, Tzu-Hsua
Abstract: Brick is one of the most common traditional building materials in the world. Located at the foot of the Bagua Mountain in Changhua, Taiwan, Qiaotou community residents make good use of mountain clay to develop the brick kiln industry, and once created a glorious history. With the increase in building materials regulations, the chimneys of brick kilns no longer smoke, and the industry has gradually declined. This study hopes that the traditional brick kiln industry will be improved through technological technique and input a new generation of innovative thinking. The general brick kiln cultural products will be re-granted to new life from the decline and showing the creative thinking in the local culture. The materials test method was used to study the processing technology of brick powder. It is expected to improve the precision of brick products and reduce the production cost through the application of the powder metallurgy process technique. And applied to the brick creative culture product design to create unique merchandise.